Implementation of lean leadership Implementation of lean leadership = Realizacja lean leadership - Trenker, Małgorzata (Zielona Góra: Faculty of Economics and Management Press)
The Toyota case proves that lean leadership is of critical importance for the successful implementation and permanent functioning of Lean Production System. There is no ready formula for developing Toyota style lean leadership. However, one may gain inspiration from its experience. Practice shows that many implementations of Lean Management do not meet expectation in the long term.
Keywords: przywództwo w Lean; szczupłe zarządzanie; system szczupłej produkcji; ciągłe doskonalenie; Lean leadership; lean management; Lean Production System; continuous improvement